Factors affecting financial well-being: the mediating role of financial behavior towards religiosity and anti-consumption lifestyle – evidence from Indonesia - Arief Budiyanto; Abdul Mujib; Mohammad Nur Rianto Al Arif; Riris Aishah Prasetyowati (Investment Management & Financial Innovations)
Research on financial well-being not only employs objective measures such as income, but also utilizes a psychological approach to measure subjective well-being, which is beneficial for alleviating stress stemming from financial conditions, enhancing overall mental health, and augmenting individuals’ quality of life. This study devises a metric for financial well-being, incorporating variables such as religiosity, anti-consumption lifestyle, and financial behavior through a quantitative approach using Structural Equation Model. The research model is examined using LISREL 8.0 for data analysis drawn from a questionnaire administered to 256 Muslim respondents. The research findings revealed that good financial behavior is the main key to achieving better financial well-being, with support from an anti-consumerist lifestyle towards such financial behavior. Meanwhile, religiosity does not significantly influence financial behavior. While religiosity can have a direct positive effect on financial well-being, it does not do so through the mediation of financial behavior. An anti-consumption lifestyle itself does not directly affect financial well-being without the help of mediating supportive financial behavior. The practical implications of these research findings suggest that financial education programs should not only focus on the aspect of religiosity alone, but also be practical and applicable to all individuals regardless of their level of religiosity.